Enhanced Acetone-Sensing Properties of PEI Thin Film by GO-NH2 Functional Groups Modification at Room Temperature - Zhao, Qiuni; He, Zaizhou; Jiang, Yadong; Yuan, Zhen; Wu, Hongru; Su, Chenliang; Tai, Huiling (Frontiers in Materials, 2019)
The functional groups of organic gas-sensing materials play a crucial role in adsorbing specific gas molecules, which is significant to the sensing performances of gas sensor. In this work, amido-graphene oxide (GO-NH2) loaded poly(ethyleneimine) (PEI) composite thin film (PEI/GO-NH2) with abundant amino functional groups -NH2 was successfully prepared on quartz crystal microbalance (QCM) by a combined spraying and drop coating method for acetone detection at room temperature (25℃). The morphological, spectrographic and acetone-sensing properties of composite film were investigated. The results demonstrated that a wrinkled surface morphology was formed and the ratio of nucleophilic -NH2 was increased for PEI/GO-NH2 composite film. Meanwhile, the composite film sensor possessed excellent acetone-sensing performances, and its sensitivity was about 4.2 times higher than that of pure PEI one owing to the increased -NH2 groups. This study reveals the important role of absorbing favorable functional groups and provides a novel method for the rational design and construction of acetone-sensing materials.